The BiPo-3 detector. (May 2017) - Loaiza, P.; Barabash, A.S.; Basharina-Freshville, A.; Birdsall, E.; Blondel, S.; Blot, S.; Bongrand, M.; Boursette, D.; Brudanin, V.; Busto, J.; Caffrey, A.J.; Calvez, S.; et al.
Abstract: The BiPo-3 detector is a low radioactive detector dedicated to measuring ultra-low natural contaminations of 208 Tl and 214 Bi in thin materials, initially developed to measure the radiopurity of the double β decay source foils of the SuperNEMO experiment at the μBq/kg level. The BiPo-3 technique consists in installing the foil of interest between two thin ultra-radiopure scintillators coupled to low radioactive photomultipliers. The design and performances of the detector are presented. In this paper, the final results of the 208 Tl and 214 Bi activity measurements of the first enriched 82 Se foils are reported for the first time, showing the capability of the detector to reach sensitivities in the range of some μBq/kg. Abstract : Highlights: BiPo3 : low radioactive detector to measure ultra-low levels of 208 Tl and 214 Bi. Backgrounds characterized. Surface background : A( 208 Tl) =(0.9±0.2) μBq/m 2 and A( 214 Bi) =(1.0±0.3) μBq/m 2 . First SuperNemo double β source foils measured : A( 208 Tl) =(21±11) μBq/kg and A( 214 Bi) < 290 μBq/kg at 90% C.L. Shows capability to measure 208 Tl in the range of some μBq/kg.